Penerjemahan Adaptasi Subtitle Lagu dalam Album Tabassam yang Dipopulerkan oleh Mesut Kurtis - Amelia Abnah; Darsita Suparno; Mauidlotun Nisa (Universitas Sebelas Maret, 2023)
This study aims to translate songs popularized by Mesut Kurtis in the Tabassam Album. The data of this research are six songs (Tabassam - تَبَسَّمْ, Rouhi Fidak - روْحِيْ فِدَاكْ, Ghar Hira - غَار حِرَاء, Ataytu Bithanbi - أَتَيْتُ بِذَنْبِيْ, Farha - فَرْحَةُ, dan Adnani - عَدْنَانِي) by using the adaptation translation method. After the song is translated, then edited using the VN (Video Editor) application, the video karaoke system is uploaded to the Youtube application. The method used in this research is a qualitative-descriptive method. The results of this study are that the adaptation translation that is carried out is more inclined to adapt aspects of Indonesian language literature by choosing a diction with the same vowel or consonant sound at the end of the song's stanza for example ‘Kenapa kau mempersulit hidupmu sendiri?’ then the next line, ‘Putus asa dan bersedih hati’, both end in the vowel -i. Therefore, in the context of translating this tabassam album, the researcher adapted it by harmonizing the rhymes or the final sound because in this context it describes the Prophet Muhammad and Allah SWT who are universal, so there are no different cultural elements in this song.